Community-based flood disaster management for older adults in southern of Thailand: A qualitative study - Pairin Yodsuban; Khanitta Nuntaboot (International Journal of Nursing Sciences, 2021)
Objective: This study explored the approaches for community-based flood disaster management for older adults in Southern Thailand. It sought to understand community culture for supporting older adults and promoting community strength in case of flood disaster. Method: This was a qualitative content analysis study using data from observation, in-depth interviews, secondary data, and focus group discussion. One hundred and twenty-seven people in total were selected specifically for the study, including Local Administration Organization (LAO), community leaders, public sector officers, civil groups, and older adult groups and family caregivers. Results: The results of this study were two main themes, focusing on 1) approaches to community-based flood disaster management for older adults as follows: eight approaches in the phase of prevention and preparedness in flood disaster management for older adults, eight approaches in the phase of response in flood disaster management for older adults, and six approaches in the phase of recovery and rehabilitation in flood disaster management for older adults; and 2) factors contributing to success in flood disaster management for older adults has four factors, including the human factor, the work factor, the data factor, and the resource factor. Conclusion: The findings showed significant roles in improving the potential and strength in community-based flood disaster management for older adults and providing suggestions for community nurses and health practice personnel involving in flood disaster management to mitigate the potential influence on older adults in the community.